ANTIOXIDANT AND ANTlMICROBIAL ACTIVITIES OF FERULIC ACID ESTERS FROM Ochrosia Oppositifolia - Fadaei Nasab, Mehran; A.Hadi, A.Hamid; A. Najmuldeen, Ibrahim; Awang, Khalijah; Sohrab, Ali Dadolahi; Ebrahimi, Reza Farzin; Rafat, Arash; Khorasan, Arash (Malaysian Journal of Science, 2011)
Two ferulic acid esters namely (E)-methyl 3-(4’-hydroxy-3’,5’ dimethoxyphenyl) acrylate1 and (E)-methyl 18-((E)-3-(4’-hydroxy-3’methoxyphenyl)acryloyloxy)octadec-3-enoate ) 2, were isolated from Ochrosia oppositifolia. The compound 1 ,and 2 and the crude methanol and hexane extracts of Ochrosia oppositifolia showed a moderate in vitro antioxidant and antimicrobial activity. ( Keywords: Ochrosia oppositifolia, Apocynaceae, Ferulic acid esters, antimicrobial and antioxidant)